Knowledge and propagation of the third generation behavior therapies among Spanish psychologists - Zych, Izabella; Buela Casal, Gualberto; Sierra, Juan Carlos; Gómez Rodríguez, Sergio (Anales de Psicología / Annals of Psychology, 2012)
The third generation behavior therapies are gaining importance and are considered advanced psychological treatments. Thus, their know- ledge and propagation seem to be necessary. The current work is an answer to this necessity. The questionnaire on knowledge and propagation of the third generation behavior therapies was answered by 274 Spanish psychologists from 15 autonomous communities. Utilizing the multidimensional analysis, the distribution of the sample was studied with respect to the knowledge and application of these therapies, together with variables such as the age, autonomous community and the professional experience. The results show that only few of the evaluated psychologists know the third generation behavior therapies. Moreover, even in case of the best known, Acceptance Commitment Therapy, 74.82% have heard speaking about it but only 16.42% apply the therapy. Nevertheless, it was also shown that there are psychologists who know well and apply these therapies. It is concluded that knowledge and propagation of the third generation behavior therapies are not sufficient and there is a necessity to educate the professionals in the subject.